2005
DOI: 10.1007/s10750-005-2742-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effects of Elevated Sea-Water Temperature on Pelagic Food Webs

Abstract: The effect of temperature changes on the marine pelagic food web was studied in three successive mesocosm experiments, performed during the spring bloom 2001 in the northern Baltic Sea. The temperature was varied from 5 to 20°C in each experiment, running over a 3-week period. The experiments included food webs of at least four trophic levels: (1) phytoplankton-bacteria, (2) flagellates, (3) ciliates and (4) metazooplankton. The results showed that heterotrophic to autotrophic biomass ratio (H/A) increased 5 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
62
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 38 publications
13
62
4
Order By: Relevance
“…3A,B & 4G,H). The observed trends of chl a concentration agree with Müren et al (2005), who found the high-est phytoplankton biomass at 5.0°C, which then decreased with higher temperatures and reached a minimum at 10.0°C. In the same experimental microcosms as ours, A. Coello-Camba (un publ.)…”
Section: Phytoplankton and Bacterioplanktonsupporting
confidence: 89%
“…3A,B & 4G,H). The observed trends of chl a concentration agree with Müren et al (2005), who found the high-est phytoplankton biomass at 5.0°C, which then decreased with higher temperatures and reached a minimum at 10.0°C. In the same experimental microcosms as ours, A. Coello-Camba (un publ.)…”
Section: Phytoplankton and Bacterioplanktonsupporting
confidence: 89%
“…Therefore, the reduced biomass accumulation under higher temperatures has to be explained by intensified grazing or other removal processes of primary production (e.g., cell lysis, sinking). This effect was also found in other locations, for example, in coastal ecosystems of South Carolina (O'Connor et al 2009) and in the northern Baltic Sea (Müren et al 2005). Copepod grazing as a component of the heterotrophic losses also had a negative effect on phytoplankton peak biomass, but the importance of this factor should not be overestimated: The multiple regression with three variables (ln L, ln C, ln B 0 ) explained just as much of the total variance as the Michaelis-Menten-model with light alone (r 2 = 0.97).…”
Section: Discussionsupporting
confidence: 73%
“…This effect is enhanced at the primary producer level if heterotrophic processes are Mar Biol (2012) 159:2367-2377 2371 123 more strongly accelerated by warming than photosynthesis, as shown by an overview of Q 10 -data in Sommer and Lengfellner (2008). This prediction was supported by the mesocosm experiments by Müren et al (2005) and O'Connor et al (2009). Within AQUASHIFT, the Baltic Sea mesocosm experiments (Klauschies et al 2012;Sommer et al 2012;Winder et al 2012), the microcosm experiments of Burgmer and Hillebrand (2011), and modeling Lake Constance phytoplankton (Tirok and Gaedke 2007b) also showed a declining phytoplankton biomass, while the lake mesocosms did not show a decline of phytoplankton biomass under warmer conditions (Sebastian et al 2012;Winder et al 2012).…”
Section: Changes In Biomassmentioning
confidence: 76%